Nonlinear fracture dynamics of double cantilever beam sandwich specimens - Burlayenko, V. N.; Sadowski, Tomasz; Dimitrova, Svetlana (Sapienza University of Rome, 2019)
A virtual testing of double cantilever beam interlaminar fracture toughness sandwich specimens under different types of dynamic loads and loading rates is considered. The nonlinear dynamic response of those sandwich specimens being fractured during the test is numerically examined using the two-dimensional finite element model within the ABAQUSTM code. The interaction integral method is exploited to extract the dynamic stress intensity factor. Cohesive elements allocated along the face/core interface are used to simulate the dynamic fracturing of the specimens.
Keywords: dynamic stress; stress intensity factors; finite element method; energy release rate; double cantilever beam